Soil Fertility and Crop Recommendation using Machine Learning and Deep Learning Techniques: A Review - Jagruti Raut, Dr. Sonu Mittal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Agriculture plays an important role in the economic growth of the nation. The agriculture sector has benefited by the rapid advancement in the area of Artificial Intelligence and Big Data. Machine Learning is the core subarea of Artificial Intelligence which provides the ability of self-learning without explicit programming.The application of Machine Learning techniques in the various fields had increased rapidly. Various Machine Learning algorithms have been applied for research in the areas of Agriculture. This study aims to provide a comprehensive review of different Machine Learning and Deep Learning techniques used in prediction of Soil Fertility and Crop Recommendation. The soil fertility rate is predicted by using soil micronutrients and macronutrients. We found that there is increasing usage of Machine Learning and Deep Learning Techniques in the area of Soil Science. Ensemble methods usually perform much better than the simpler approaches.